2016
DOI: 10.1016/j.jbiomech.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles released from tumor cells disrupt epithelial cell morphology and contractility

Abstract: During tumor progression, cancer cells interact and communicate with non-malignant cells within their local microenvironment. Microvesicles (MV) derived from human cancer cells play an important role in mediating this communication. Another critical aspect of cancer progression involves widespread ECM remodeling, which occur both at the primary and metastatic sites. ECM remodeling and reorganization within the tumor microenvironment is generally attributed to fibroblasts. Here, using MCF10a cells, a well-chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…This may also arise from the mesenchymal cell line used here (MDA-MB-231), which has been observed to secrete exosomes that reprogram epithelial cells (MCF-10A) to undergo EMT. 51, 52 Finally, co-cultured primary liver hepatocytes have been observed to reprogram mesenchymal cell line (MDA-MB-231) to undergo MET. 53 We see some less elongation and vimentin expression in co-cultured MDA-MB-231 cells, but additional measurements of epithelial biomarkers are necessary to establish conclusively that MET is occurring.…”
Section: Discussionmentioning
confidence: 99%
“…This may also arise from the mesenchymal cell line used here (MDA-MB-231), which has been observed to secrete exosomes that reprogram epithelial cells (MCF-10A) to undergo EMT. 51, 52 Finally, co-cultured primary liver hepatocytes have been observed to reprogram mesenchymal cell line (MDA-MB-231) to undergo MET. 53 We see some less elongation and vimentin expression in co-cultured MDA-MB-231 cells, but additional measurements of epithelial biomarkers are necessary to establish conclusively that MET is occurring.…”
Section: Discussionmentioning
confidence: 99%
“…MVs released by cancer cells may contain various proteins that regulate immune responses, including chemokine receptors, proinflammatory cytokines such as IL-1 or IL-6 and cytokine receptors such as TNFR1 [320]. Cancer cells, by releasing MVs, can disrupt epithelial cell morphology and promote EMT leading to tumor progression [321]. The cargo of LOs differs from other vesicles and includes factors associated with tumor progression [322].…”
Section: Microvesicles and Oncosomesmentioning
confidence: 99%
“…Features of these MVs that support tumor growth and invasiveness are linked to interactions with the tumor microenvironment, where they can induce a tumor-supporting milieu [ 161 , 162 ]. Bordeleau et al have suggested that tumor-derived MVs could contribute to extracellular matrix reorganization by enhancing the contractility of non-malignant epithelial cells within the primary tumor and the metastatic sites [ 163 ]. Also, Taheri et al have demonstrated that glioma tumor-derived MVs can stimulate proliferative and metastatic gene expression in normal astrocytes within the tumor microenvironment, thus affecting tumor growth and invasion [ 164 ].…”
Section: Tumor-derived Mvsmentioning
confidence: 99%